2021
DOI: 10.3390/s21175785
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Multilayer Nanostructures of Magnetic Straintronics Based on the Anisotropic Magnetoresistive Effect

Abstract: The article presents the results of experimental studies of multilayer nanostructures of magnetic straintronics formed by magnetron sputtering on a 100 mm silicon wafer. The object of the study is two types of nanostructures: Ta/FeNiCo/CoFe/Ta and Ta/FeNi/CoFe/Ta, differing in the ratio of magnetic layers. The magnetic and magnetoresistive characteristics of multilayer nanostructures under varying mechanical loads are studied both on a 100 mm wafer and in the form of 4 × 20 mm2 samples of two types. The first,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This sensor geometry has enabled them to achieve a magnetic sensitivity as high as 1.25 mV Oe −1 (or 0.45 mV/V/Oe). Zhukov et al [26] have shown that the nanostructures with FeNiCo as the magnetoresistive material are superior to those with FeNi as the magnetoresistive material in terms of AMR effect and sensitivity, confirming the possibility of using multilayered nanostructures as sensitive elements in magnetically strained electronic devices. Pan et al [27] prepared nanoscale multilayers with the main structure of Ta (5 nm)/ MgO (3 nm)/ NiFe (10 nm)/ MgO (3 nm)/ Ta (3 nm) by magnetron sputtering and the 1/f noise of the sensor element was reduced by three orders of magnitude after annealing the film for 7200 s at 400 • C. Jiang et al [28] designed a two-axis, sensitive AMR magnetic field sensor.…”
Section: Introductionmentioning
confidence: 97%
“…This sensor geometry has enabled them to achieve a magnetic sensitivity as high as 1.25 mV Oe −1 (or 0.45 mV/V/Oe). Zhukov et al [26] have shown that the nanostructures with FeNiCo as the magnetoresistive material are superior to those with FeNi as the magnetoresistive material in terms of AMR effect and sensitivity, confirming the possibility of using multilayered nanostructures as sensitive elements in magnetically strained electronic devices. Pan et al [27] prepared nanoscale multilayers with the main structure of Ta (5 nm)/ MgO (3 nm)/ NiFe (10 nm)/ MgO (3 nm)/ Ta (3 nm) by magnetron sputtering and the 1/f noise of the sensor element was reduced by three orders of magnitude after annealing the film for 7200 s at 400 • C. Jiang et al [28] designed a two-axis, sensitive AMR magnetic field sensor.…”
Section: Introductionmentioning
confidence: 97%